2010
DOI: 10.3989/scimar.2010.74n2339
|View full text |Cite
|
Sign up to set email alerts
|

Feeding on protists and particulates by the leptocephali of the worm eels <i>Myrophis</i> spp. (Teleostei: Anguilliformes: Ophichthidae), and the potential energy contribution of large aloricate protozoa

Abstract: SUMMARY:The food sources of the leptocephali of the teleostean superorder Elopomorpha have been controversial, yet observations on the leptocephali of the worm eels, Myrophis spp. (family Ophichthidae) collected in the northern Gulf of Mexico indicate active, not passive, feeding. Leptocephali had protists in their alimentary canals. Estimates of the physiological energetics of worm eels indicate that large aloricate protozoa including ciliates could provide substantial energy to these leptocephali toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…Based on his comprehensive review of leptocephalus feeding ecology, Miller [8] seemed fairly convinced that marine snow-like material is the major food for leptocephali. The present study detected no specific DNA common to leptocephalus larvae, and previous studies reported a wide variety of small organisms, larvacean houses, and fecal pellets as food [23], [24]. This corresponds to Miller's implication and is further corroborated by stable isotope ratio analysis on the eel leptocephali and POM [21], [28].…”
Section: Discussionsupporting
confidence: 87%
“…Based on his comprehensive review of leptocephalus feeding ecology, Miller [8] seemed fairly convinced that marine snow-like material is the major food for leptocephali. The present study detected no specific DNA common to leptocephalus larvae, and previous studies reported a wide variety of small organisms, larvacean houses, and fecal pellets as food [23], [24]. This corresponds to Miller's implication and is further corroborated by stable isotope ratio analysis on the eel leptocephali and POM [21], [28].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, unidentified gut contents were observed in 27% of leptocephalus specimens (of the five dominant species) examined from off NC. Although we did not detect any food items in the guts of the dominant species of leptocephali in the GOM, Govoni () reported protists in the guts of GOM Myrophis spp. We would not have been able to observe protists, bacteria and other microscopic organisms in the digestive tracts if those were some of the main sources of food for the dominant leptocephalus species in the GOM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined dietary habits of larvae and elvers of M. punctatus and revealed a progressive change from a planktivorous to a zoobenthivorous diet (Mochioka & Iwamizu, 1996; Duque, 2004; Govoni, 2010). This study provides information on the diet of juveniles after their recruitment to coastal habitats of the IRL.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment from pelagic to shallow coastal waters and the metamorphosis from leptocephali to juveniles coincide with a change of feeding habits and habitats. Leptocephalus larvae are planktivores and consume harpacticoid copepods, ostracods, diatoms and protozoa such as aloricate ciliates (Duque, 2004; Govoni, 2010). In the coastal waters of Louisiana, M. punctatus elvers rely primarily on organic matter from salt marshes (Duque, 2004).…”
Section: Introductionmentioning
confidence: 99%